Depth profiles of aluminum component in sequential infiltration synthesis-treated electron beam resist films analyzed by time-of-flight secondary ion mass spectrometry. (7th May 2020) - Ito, Shunya; Ozaki, Yuki; Nakamura, Takahiro; Nakagawa, Masaru
Abstract: Sequential infiltration synthesis (SIS) is a promising method for organic–inorganic hybridization of organic polymer resist films in nanolithography. The understanding of the distribution of inorganic components in hybrid films is necessary for the practical use of SIS-treated resist films. In this study, we investigated the distribution of aluminum oxide in SIS-treated positive-tone electron beam resist films of poly(methyl methacrylate) and ZEP520A with thicknesses of 100, 40, and 20 nm by time-of-flight secondary ion mass spectrometry (TOF-SIMS). TOF-SIMS profiles revealed that the aluminum species of AlO − and AlO2 − derived from aluminum oxide existed heterogeneously near the air/polymer surface, film inside, and polymer/substrate interface, and the distributions of respective species depended on film thickness. TOF-SIMS enabled the characterization of aluminum distribution in 20 nm thick resist films. It was suggested that the oxidation states of Al components were different between near the air/polymer surface and near the polymer/substrate interface.